Investigating the Dehumidification Characteristics of Turbine Stator Cascades with Parallel Channels - Zhonghe Han; Wei Zeng; Xu Han; Peng Xiang (Energies, 2018)
Steam turbines play a vital role in the power industry. The efficiency of the steam turbine can be improved by reforming the flow structure. For the White cascade, a parallel channel which is an additional steam passage was designed to connect adjacent steam flow channels. In view of the steepening and sensitive characteristics of the steam condensation parameters in the White cascade, the two-fluid model was applied to study the condensation and aerodynamic characteristics of the prototype cascade and the modified cascade. Wetness losses were regarded as the evaluation standard, and the optimum design of the parallel channel was obtained. The influence of channel width was also studied. The location of the suction surface (D point) has great influence on the dehumidification performance of the cascade. On the contrary, the location of the pressure surface (C point) has no significant effect on dehumidification performance. Moreover, it is necessary to select the width of the parallel channel in combination with the cascade performance. It is suggested that the parallel channel width should be between 3 and 5 mm. The research results can provide a reference for the optimal design of a turbine stator cascade.